INTELLIGENCE ANALYSIS THAT INFLUENCES ON CONFLICT MANAGEMENT IN THE DIGITAL ERA - Cahyani, Diah; Cahyaning Pratiwi, Elok; Nuraeni, Eny; Sunaryo, Agus (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study analyzes intelligence influencing conflict management in the digital era. This research is descriptive-explorative. The research location at the PKL Center Jl. Benteng Pancasila City of Mojokerto. The population of 369 MSME actors with the Slovin formula of 0.01 was determined by 79 respondents. Data collection using a questionnaire. Data analysis using SmartPLS version 3.3.7. Test the hypothesis by comparing the T-Statistics and P-Values. The results of this study are: communication intelligence, creative intelligence, and emotional intelligence have a significant effect on conflict management, social intelligence, and strategic intelligence has no effect on conflict management, communication intelligence, creative intelligence, emotional intelligence, social intelligence, and strategic intelligence simultaneously influence conflict management. Research recommendation: Combining this intelligence can resolve conflicts effectively and efficiently and avoid further damage to relationships.